Efficacy, safety and prognostic features of resected colon carcinoma treated in real world practice: a retrospective cohort-study - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2011)
Purpose: Treatment outcomes and prognostic features of a specific cancer generally come from prospective randomized studies. It seems reasonable to ask the question whether the results of prospective randomized studies entirely reflect the results of the population treated in real world practice. Therefore we performed a retrospective cohort analysis in order to find out the efficacy of adjuvant chemotherapy as well as the prognostic factors of our patient population treated in daily practice, and compared these findings with those defined in the prospective studies. Methods: Data of patients with high risk stage II and all stage III colon cancers treated with adjuvant chemotherapy were retrospectively analyzed. Results: A total of 190 patients were retrospectively analyzed. The rates of T2, T3, and T4 tumors were 4.2, 77.9, and 17.9%, respectively. Over 35% of the patients had stage II disease. Of the 5-fluorouracil (5-FU)-based chemotherapy group (n=141), 15% had a dose reduction because of toxicily and 73% were given the total planned dose and cycles, whereas these rates were 18.5 and 66% for oxaliplatin+5-FU treated group, respectively (p=0.66 and 0.44, respectively). The 3-year disease-free survival (DFS) and 5-year cancer-specific overall survival (OS) for all patients were 69.4 and 73%, respectively. In multivariate analysis, cancer-specific OS showed significant correlation with T stage (p=0.015) and with perineural invasion (p=0.024). Also patients >= 65 years old had significantly lower OS (p=0.003) Conclusion: This study is the first to report the efficacy of adjuvant treatment in a curatively resected Turkish colon carcinoma population treated in real world practice. Our study showed that the treatment results and the prognostic parameters of Turkish colon carcinoma patients treated in real world practice are not different from those of selected patients treated in randomized prospective studies.
Keywords: adjuvant treatment; colon cancer; fluorouracil; oxaliplatin; real world; POSTOPERATIVE ADJUVANT THERAPY; AMERICAN JOINT COMMITTEE; COLORECTAL-CANCER; STAGE-II; ELDERLY-PATIENTS; POOLED ANALYSIS; TUMOR-MARKERS; FLUOROURACIL; CHEMOTHERAPY; LEUCOVORIN